IMPLEMENTASI NILAI TAUHID DALAM SISTEM MANAJEMEN PENDIDIKAN ISLAM DI MASYARAKAT MODERN - Salamah, Salamah (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This article aims to analyze the implementation of tauhid values in the Islamic education management system amid the dynamics of modern society. Modernization brings social, cultural, and moral changes that affect the orientation of education. Tauhid values, as the core of Islamic teachings, must be the basis in every aspect of education management so that Islamic educational institutions are not only oriented towards academic achievement but also towards character building and spirituality of students. This study uses a qualitative approach with a literature review method. The results of the study show that tauhid values can be implemented in education management through the dimensions of planning, organizing, implementing, and evaluating education. The integration of tauhid values makes Islamic education management more oriented towards a balance between worldly and spiritual aspects, intellectual and moral aspects, as well as individual and social aspects